Valuation Effects of Greenmail Prohibitions - Eckbo, B. Espen (Journal of Financial and Quantitative Analysis, 1990)
Greenmail payments are widely viewed as actions designed by managers to perpetuate their tenure in office. This view, which suggests that greenmail prohibitions would enhance shareholder wealth, receives mixed empirical support in this paper. The average market reaction to charter amendments prohibiting greenmail payments is weakly negative, suggesting there is a value to maintaining managerial flexibility. Nonlinear maximum likelihood estimation, however, reveals a strong positive correlation between the market reaction and the firm's abnormal stock price runup over the three months just prior to the proxy mailing date. For the subsample of firms with a relatively large prior runup, the precommitment not to pay greenmail is value enhancing. If the prior runup reflects takeover rumors, then this evidence is consistent with the proposition that greenmail payments amidst takeover speculations are value decreasing.